AQMI: Software for assessing the quality of mammographic images (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Objective: AQMI - “Assessment of the quality of mammographic images” was developed to support the quality control (QC) of digital mammographic images. Materials and Methods: The software was implemented in the Python programming language via the Streamlit library, which involved content structuring and environmental planning. The experimental data that were selected from a public domain repository [19]. From the selected database, relevant information that was present in the DICOM file was studied to perform the image quality test. Then, from searching the literature, indicators that measure image quality were found, such as the signal-to-noise ratio, the contrast-to-noise ratio, figure of merit and image histogram. Results: AQMI assists in analyzing the image quality test established in IN 92 by the Agência Nacional de Vigilância Sanitária [8]. It also has quality addition indicators, trend graphs, and the image assessment history. Conclusion: For the functionalities of this work, the developed software is a promising tool for use in clinical practice, since it consists of a free, friendly, and easy-to-use interface.